2007
DOI: 10.1051/0004-6361:20066792
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the internal structuring of coronal loops on the properties of their damped transverse oscillations

Abstract: Context. The geometry and physical conditions in solar coronal loops are complicated and still not understood well. Recent highresolution observations obtained with TRACE indicate the existence of sub-resolution transverse structuring not accessible to direct observation. This ingredient has not yet been taken into account in the previous theoretical models used for the study of transversal coronal loop oscillations and of their damping due to resonant conversion of energy. Aims. This study aims to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 39 publications
4
39
2
Order By: Relevance
“…We also found that the damping rate due to resonant absorption is sufficiently reduced by the tube interaction. This difference between our results and those by Arregui et al (2007) is not very surprising. As we have already noted, the properties of kink oscillations of single slabs and tubes are quite different.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…We also found that the damping rate due to resonant absorption is sufficiently reduced by the tube interaction. This difference between our results and those by Arregui et al (2007) is not very surprising. As we have already noted, the properties of kink oscillations of single slabs and tubes are quite different.…”
Section: Discussioncontrasting
confidence: 98%
“…It is interesting to compare our results with those obtained by Arregui et al (2007). In their study of resonantly damped kink oscillations of the system of two parallel slabs these authors found that the properties of kink oscillations of this system and the damping time are practically the same as of a single slab with the equivalent parameters.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…This result is consistent with that of Russell & Wright (2010) who demonstrated the persistence of resonant wave coupling in equilibria with a two-dimensional structure perpendicular to the background magnetic field. Arregui et al (2007b) also considered the effect of internal density structuring of a coronal loop on its oscillatory properties using a two-slab model. They found that the internal structure did not significantly affect the features of the resonantly damped fast mode oscillations (see also Goossens et al 2008).…”
Section: Introductionmentioning
confidence: 99%